The risks of self-medication (International Seven Journal of Multidisciplinary, 2024)
Drugs have marked a great revolution in public health activities, being most often used as the first option in current therapy. However, the stimulus of the media and the ease of acquisition ended up making their use routine, thus generating accumulation of these products in homes, and consequently self-medication. Because there is a need to promote the education of the population in relation to the rational use of medications, showing the risks of self-medication, the present study was carried out. The main objective of this study was to present a literature review on home pharmacy and the risks of self-medication. For this, a search in the national and international literature was carried out through the Scielo, Lilacs and MEDLINE/PubMed databases. It was emphasized that home pharmacy is very common in most homes, and that the practice of self-medication is very frequent, this is due to the easy access to medicines, in addition to the popular culture of obtaining, through natural means, a medicine, such as plant extracts. The benefits brought by making the population aware of the rational use of medicines, as well as the correct way to store them, promotes the improvement of health, thus reducing the risks of drug poisoning, in addition to the other risks that self-medication exposes the population. This attribution highlights the significant work of the pharmacist professional, as he is the holder of knowledge, who dispenses medicines and provides guidance to the patient.